2021
DOI: 10.1002/csc2.20524
|View full text |Cite
|
Sign up to set email alerts
|

Putative genes for resistance to gray leaf spot of maize based on genomic resequencing using recombinant inbred lines

Abstract: Gray leaf spot (GLS) of maize (Zea mays L.), caused by Cercospora spp., inflicts serious yield losses. Four recombinant inbred lines (RILs) were developed from the [(YML32×Q11) × Q11] backcross population. Two flanking markers, GZ204 and IDP5, defining quantitative trait locus (QTL) qRgls1 for resistance to GLS, were detected in three RILs (RL1_1, RL1_2, and RL2_1) but not in RL2_2. This QTL is located on chromosome 8 in bin 8.02. The field resistance of RL2_2 was, however, similar to that of RL1_1 and RL1_2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The presence of qtl_Q11_2 revealed that alleles from the susceptible parental line may contribute to increased resistance. Xu et al ( 2021 ) identified a specific fragment that was resistant to maize gray spot disease from the susceptible parent Q11. This demonstrates the complexity of the genetic mechanisms underlying the quantitative traits of plants.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of qtl_Q11_2 revealed that alleles from the susceptible parental line may contribute to increased resistance. Xu et al ( 2021 ) identified a specific fragment that was resistant to maize gray spot disease from the susceptible parent Q11. This demonstrates the complexity of the genetic mechanisms underlying the quantitative traits of plants.…”
Section: Discussionmentioning
confidence: 99%